Penerapan Metode Qiraati dalam Kegiatan Membaca Al-Qur’an pada Anak Usia 3-5 Tahun di TPQ Sahabat Qurani Bekasi - Niola Dinda Maharani; Roza Yenita; Rhoma Iskandar (Jurnal Teologi Islam, 2025)
Teaching Qur'an reading to children aged 3–5 faces challenges due to limited attention spans and conventional methods that fail to engage young learners. The Qiraati method offers a structured and interactive approach, yet its application in early childhood education remains underexplored. This study examines the implementation of the Qiraati method in Qur'an reading activities for children aged 3–5 at TPQ Sahabat Qurani Bekasi. Using a descriptive qualitative approach, data were collected through observation, interviews, and document analysis. Findings indicate that the Qiraati method effectively enhances children’s ability to recognize Hijaiyah letters and pronounce them with correct makharij. The method was implemented in two main stages: classical learning with visual aids and individual learning using a read-listen technique. Key supporting factors included teacher competency and parental involvement, while challenges included children’s short attention spans and limited instructional media variety. The study concludes that the Qiraati method proves effective in creating meaningful and engaging learning experiences for young children. These findings contribute to the development of adaptive Qur'an learning models for early childhood education.